Highly Nonlinear Multimode Tellurite Fibers: From Glass Synthesis to Practical Applications in Multiphoton Imaging. Issue 1 (9th December 2022) - Evrard, Marianne; Mansuryan, Tigran; Couderc, Vincent; Désévédavy, Frédéric; Strutynski, Clément; Dussauze, Marc; Arosa Lobato, Yago; Tonello, Alessandro; Colas, Maggy; El-Dib, Georges; Danto, Sylvain; Cardinal, Thierry; et al.
Abstract : Herein, a tellurite multimode optical fiber with a rectangular step‐index core to combine easy coupling of the pump power with the exceptionally cubic nonlinearity of such type of glass is developed. An alkali‐free composition (TeO2 –ZnO–La2 O3 ) is prepared to produce a preform with the use of both the stack‐and‐draw and the direct‐bonding methods. The linear and nonlinear optical responses of the fiber are characterized and are then used to generate a homogeneous supercontinuum (SC) in the near‐infrared domain. The spectral broadening, which is obtained in this work in a short fiber sample, is used for imaging mouse kidney cells, labeled with three different fluorochromes, by means of two‐photon absorption (2PA) and three‐photon absorption (3PA). Despite the multimode nature of the output beam, clear images of tubules, actin, and nucleus are collected with a spatial resolution down to 1.2 μm. Although image acquisition at better resolution has already been reported in the literature using relatively long spans of graded‐index silica multimode fibers, here, the combination of high third‐order susceptibility of the glass and the large Raman gain in short segments of tellurite fiber is exploited to obtain nonlinear imaging with adequate spatial resolution. Abstract : Cubic nonlinearity of a manufactured tellurite multimode optical fiber with a rectangular core is exploited to generate a homogeneous supercontinuum (SC) in the near‐infrared. This allows to perform two‐photon absorption (2PA) and three‐photon absorption (3PA) nonlinear fluorescence imaging and to obtain clear images of mouse kidney cells by reaching an acceptable spatial resolution of 1.2 μm, with short segments of fiber.